Sustainable Health Care Financing: The Singapore Experience. (March 2017) - Lim, Jeremy
Abstract: The Singapore health system has been lauded for achieving impressive population health outcomes utilizing only a modest 4–5 per cent of GDP, with the government's share only one third of this. Measured health spending is consistent with a larger government commitment to fiscal prudence and discipline in balancing budgets. In fact, the Singapore constitution permits a government to only spend revenue raised during its term of office. Drawing down of national reserves can only be done during exceptional circumstances and requires specific approval from the president. However, the sustainability of Singapore's health system is under pressure from changing demographics, disease trends and growing demands from citizens for greater equity and expanded health care services. In the face of these challenges, the Singaporean government has responded by introducing three major costly policy reforms: the Pioneer Generation Package, to help elderly people pay for medical treatment; MediShield Life, to expand insurance coverage; and the Community Health Assistance Scheme (CHAS), to provide government subsidies for primary care for those that qualify. Despite the expansion of funding and services, the government remains committed to the longstanding principles of fiscal prudence and not drawing from past reserves. Abstract : As the government actively strives to close the income inequality gap and offer stronger social safety nets in healthcare, it remains mindful of the risk of over‐exuberance in public spending.